Platelet-Derived Growth Factor-BB Inhibits Intervertebral Disc Degeneration via Suppressing Pyroptosis and Activating the MAPK Signaling Pathway - Zhang, Weikang; Gong, Yuhang; Zheng, Xiaohang; Qiu, Jianxin; Jiang, Ting; Chen, Lihua; Lu, Fangying; Wu, Xinhui; Cheng, Fengmin; Hong, Zhenghua (Frontiers in Pharmacology, 2022)
Platelet-derived growth factor-BB is a cytokine involved in tissue repair and tumor progression. It has been found to have expression differences between normal and degenerative intervertebral discs. However, it is not clear whether PDGF-BB has a protective effect on intervertebral disc degeneration. In this experiment, we treated nucleus pulposus cells with IL-1β to simulate an inflammatory environment and found that the extracellular matrix anabolic function of NPCs in an inflammatory state was inhibited. Moreover, the induction of IL-1β also enhanced the expression of NLRP3 and the cleavage of caspase-1 and IL-1β, which activated the pyroptosis of NPCs. In this study, we studied the effect of PDGF-BB on IL-1β-treated NPCs and found that PDGF-BB not only significantly promotes the extracellular matrix anabolism of nucleus pulposus cells, but also inhibits the occurrence of pyroptosis and the production of pyroptosis products of nucleus pulposus cells. Consistent with this, when we used imatinib to block the PDGF-BB receptor, the above-mentioned protective effect disappeared. In addition, we found that PDGF-BB can also promote the extracellular matrix anabolism of NPCs by regulating the ERK, JNK, PI3K/AKT signaling pathways, but not the P38 signaling pathway. In vivo studies, mice that blocked PDGF-BB receptors showed more severe histological manifestations of intervertebral disc degeneration. In summary, our results indicate that PDGF-BB participates in inhibiting the occurrence and development of IDD by inhibiting pyroptosis and regulating the MAPK signaling pathway.